Hubungan Gaya Komunikasi Kepemimpinan yang Efektif dalam Pengambilan Keputusan di Kantor Pegadaian Maumere Kabupaten Sikka - Vikor Eko Transilvanus; Angela Felisitas Ina Ritan; Arnoldus Yansen; Ega Selviani; Sisilia Sila; Theresia Yunita (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the relationship between leadership style and effective communication in the decision-making process within an organizational environment. The leadership style applied by a leader is highly instrumental in determining the quality of communication established between the leader and employees. Effective communication characterized by the clear transmission of information, openness to input, and the ability to listen actively can enhance the accuracy of information, speed, and quality of decisions made. Using a qualitative descriptive approach, this research illustrates how leaders employ specific communication styles to foster employee engagement, strengthen coordination, and minimize misunderstandings during the decision-making process. The findings indicate that the more effective the leader's communication style, the better the quality of the resulting decisions, as the process involves a transparent, participatory, and responsive exchange of information. Thus, effective communication is a key element connecting leadership style with successful decision-making within an organization.